1995
DOI: 10.1002/eji.1830250413
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the p70zap tyrosine protein kinase in T cells by the CD45 phosphotyrosine phosphatase

Abstract: Two classes of protein tyrosine kinases (PTK) are utilized by the T cell antigen receptor (TcR)/CD3 complex for initiation of the signaling cascade, the Src-family PTK p56lck and p59fyn, and the Syk-family PTK p70zap and p72syk. In addition, the CD45 phosphotyrosine phosphatase (PTPase) is required for the induction of tyrosine phosphorylation by the TcR/CD3, presumably by positively regulating Src-family PTK. Here we report that CD45 also regulates the Syk-family PTK p70zap (or ZAP-70). In CD45-negative T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 38 publications
1
34
0
1
Order By: Relevance
“…Optimal Lck activation is facilitated through Lck autophosphorylation at Y394, which also serves as a CD45 substrate. Furthermore, phosphorylated and ZAP70 have been identified as additional CD45 substrates (17,18). Although CD45 is also predicted to upregulate Lck SH3 and SH2 intermolecular ligand binding, little attention has been paid to this potential mechanism for CD45 activity (19) (see Fig.…”
mentioning
confidence: 99%
“…Optimal Lck activation is facilitated through Lck autophosphorylation at Y394, which also serves as a CD45 substrate. Furthermore, phosphorylated and ZAP70 have been identified as additional CD45 substrates (17,18). Although CD45 is also predicted to upregulate Lck SH3 and SH2 intermolecular ligand binding, little attention has been paid to this potential mechanism for CD45 activity (19) (see Fig.…”
mentioning
confidence: 99%
“…It is, however, conceivable that in response to APL stimulation, Zap-70 is recruited to the TCR-CD3 complex but maintained in an unphosphorylated and inactive form by a putative phosphotyrosine phosphatase. Candidates for such a phosphatase would include SHP-1, known to downregulate T-cell activation and Zap-70 phosphorylation (20,45), and CD45, which has been shown to interact with the chain and dephosphorylate TCR and Zap-70 in vitro (15,41). Interestingly, the pretreatment of Een217 cells with 100 nM HXB2 48 h before TCR stimulation with the agonist ligand reduced the ability of the PV22 peptide to induce TCR phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in CD45-null mice, the absolute number of DP thymocytes is reduced by about 2-fold compared with wild-type littermates, and the number of SP thymocytes is reduced by a further 5-fold (20), underscoring the importance of CD45 in T cell development. In vitro studies have shown that CD45 can dephosphorylate several substrates involved in TCR signaling, including the Src-family PTKs, Lck and Fyn, as well as CD3-and the ZAP-70 PTK (21)(22)(23)(24). The ability of CD45 to regulate the activity of Src-family PTKs, which are required for the initiation of the signal-transduction cascades associated with the TCR (25), suggests a key role for CD45 in modulating TCR-mediated signals.…”
Section: Thymic Selection Generates T Cells Expressing Self-reactivementioning
confidence: 99%